Análisis jurídico de las políticas públicas estatales en derecho económico para proteger la economía del Estado Ecuatoriano (proteccionismo económico). - Vega Sanabria, Alexandra Maribel (2024)
The relevance of this research lies in its focus on Ecuadorian policies of economic protectionism, especially in the context of the current economic crisis. Over the course of the last year, an alarming number of businesses have been shut down, approximately 20,000 statewide. These worrisome indicators were presented in an official report by Julio Prado, who holds the position of Minister of Production and Foreign Trade. This report was exposed during a cabinet meeting held at the Carondelet Palace, under the direction of the President of the Republic, Guillermo Lasso. This research proposes to examine in detail the policies adopted by Ecuador in terms of economic protectionism, considering its impact on the current economic situation and its relationship with the notable decrease in business activity in the country. Economic protectionism encompasses a set of public policies designed to regulate and safeguard a country's economy. Through their strategic application; It not only seeks to protect the national industry, but also to preserve the internal labor force. In other words, economic protectionism has as its central objective the protection of jobs and the promotion of the generation of job opportunities. This is achieved by promoting the development of the local industry, promoting the consumption of national products, implementing equitable tariffs on products of foreign origin. This establishes a dynamic in which, based on the cost-benefit relationship, consumers tend to opt for the national product. In this way, the preference for local products is strengthened, which in turn boosts internal economic activity and contributes to the economic development of the country. In the Ecuadorian market, specifically in the industry, the production and processing of products, the little development of public policies in terms of economic protectionism generates unfair competition between the national market and the foreign market, which has caused this sector of the economy Ecuador is weakened, for which it is important to create market conditions that allow the national product to compete against imported products. In the present investigation, strategic protectionist alternatives that develop a fairer market will be investigated; with a qualitative and quantitative research methodology, since the data obtained will be closer to the reality of the national market, in order to promote public policies, protecting the national industry, jobs with due restrictions regardless of free trade agreements that the national government has, through tariff taxes on products of foreign origin, with licenses and permits; until the national industries develop satisfactorily and can be competitive with the foreign one. Keywords: Economic protectionism, industry, public policies, economy, market.